Penguatan Kesadaran Politik Pada Generasi Muda dalam Menghadapi Pilkada Tahun 2024 di Kabupaten Majene - Saddam Husain Tamrin; Arifin Tahir; Syahrinullah Syahrinullah; Fajar Rakasiwi; Maria Ulfa; Ika Yuli Bhayangkari; Muhammad Sajidin; Mu'min Mu'min; Farhanuddin Farhanuddin (I-Com: Indonesian Community Journal, 2024)
As an effort to improve the quality and success of the simultaneous regional head elections (PILKADA) to be held in 2024, it is hoped that leaders can be elected who can bring progress to regions in West Sulawesi Province and Majene Regency. The success of a regional head election process cannot be separated from the level of community participation involved, and to increase public participation, it is necessary to strengthen political awareness to the community, including the younger generation, where almost 60% of the number of voters are the younger generation, so it is very important to be given strengthening political awareness to the younger generation, especially in Majene Regency. The purpose of this community service is to strengthen political awareness for the younger generation in facing the 2024 regional elections in Majene district. This service is in partnership with the National and Political Unity Agency (BAKESBANGPOL) and the Majene Regency KPU, involving lecturers and students of open universities and the University of West Sulawesi, with stages 1) Preparation; 2) Coordination with strategic partners; 3) Implementation of Focus Group Discusion 4) Carrying out socialization to strengthen political awareness among the younger generation in facing the 2024 regional elections in Majene district. The results obtained in this activity are expected to increase political awareness in the younger generation in facing the 2024 regional elections.